Uma análise do processo de constituição do Estado nacional como eixo da ascensão chinesa no capitalismo internacional - Barbieri Junior, Walter (2015)
The Chinese expansion in world capitalism has provoked a great interest in China s role in the 21st century, especially in relation to the State role in the face of the so-called market forces. Within a millenary civilization, the Chinese nation State, formally created in 1912, has been built along a process that had two milestones: the revolution triumph in 1949, whose stated goal by the main leaders was the socialist transformation, first step for the construction of a classless society; and the Four Modernization Programs, implemented by the forces led by Deng Xiaoping from 1978 on. This thesis examines more specifically the role of the Chinese nation-State building as a foundation for the expansion in world capitalism in the last thirty-five years, following the post-World War II Maoist period. In this work the author searches for the understanding of how the national ideology pervades the process of contemporary Chinese State Constitution. In addition, this study examines this State intervention in economic development of that social formation and more particularly the possibility of hegemonic rise of China in world capitalism in the 21st century